Determinants of European telecommunication operators systematic risk - Olivier Chalmeau (International Telecommunications Society (ITS), 2013)
This article studies the determinants of systematic risk for a panel of European telecommunication incumbent operators. The systematic risk (the beta coefficient) is estimated with the capital asset pricing model using different econometric methods (OLS, ML GARCH and Kalman Filter). Previous empirical literature has identified accounting variables as being determinants of systematic risk. These control variables serve as a basis to study the impact of regulation and competition on risk. The Polynomics regulatory index is used for regulation and Herfindahl-Hirschman Indexes for competition. The overall index of regulation doesn't have a clear impact on risk. However, subindexes indicating quantity regulation is associated with higher risk. By quantity, we mean regulatory constraints such as Universal service obligation or coverage obligation for mobile networks. In contrast, access regulation decreases the risk. The impact of the competition's intensity is different for the mobile and fixed markets. Results for mobile competition are not significant whereas more intense fixed competition is associated with less risk. These results are consistent with the interpretation that regulation and competition have reduced the investment of the sector. It is also consistent with the observation that competition has taken place on services rather than on infrastructures.
Keywords: 330